Factors affecting the adoption of tillage systems in Kansas - Baradi, Niranjan Kumar (Kansas State University, 2009)
Concerns about environmental degradation due to agriculture have gained importance as it is associated with soil erosion, health hazards, and ground water pollution. Environment-friendly land use practices have been developed to gain a wide range of environmental benefits including reduced soil erosion, reduced nutrient runoff from crop and livestock facilities, increased biodiversity preservation efforts, and restoration of wetlands and other native ecosystems. No-till is one such practice where soil erosion, nutrient runoff and environmental degradation can be reduced to a certain extent. This study evaluated the factors affecting the adoption of tillage systems in Kansas. A survey was conducted with a total of 135 participants from four different locations in the state of Kansas between August 2006 and January 2007. The adoption process was modeled as a two-step econometric models consisting of perception and adoption equations to estimate the impacts of demographic variables and farmers’ familiarity with and participation in certain conservation programs. The results for the perception models showed that the farm operators’ perceptions regarding whether BPM installation and management is unfair to producers or not and whether environmental legislation is often unfair to producers do not vary systematically across farm size, producers’ familiarity and participation in conservation programs, or other demographics considered in the study. On the other hand, their perceptions regarding how polluted their water supplies varied by their thoughts on relative profitability across various tillage practices, their primary occupation, and their familiarity with conservation programs. Specifically, the results suggested that those who regarded no-till practices to be more profitable than other tillage practices or whose primary occupation was farming-related tended to believe that ground water was not polluted, and those who were less familiar with available conservation programs tended to believe that surface waters were not polluted. The adoption model results suggested that farmers with greater operating acreage, those who perceived that no-till was more profitable than other tillage systems, and those with greater familiarity with and participation in existing conservation programs were more likely to adopt more conservation tillage systems, all else equal. Further, perceptions of fairness of environmental regulations or the level of pollution did not impact the tillage choices.
Keywords: Tillage; Conservation tillage; Adoption; Ordered logit model; Water quality trading; Economics, Agricultural (0503)